Molecular evolution and diversity in Bacillus anthracis as detected by amplified fragment length polymorphism markers. - Keim, P (1997)
Bacillus anthracis causes anthrax and represents one of the most molecularly monomorphic bacteria known. We have used AFLP (amplified fragment length polymorphism) DNA markers to analyze 78 B. anthracis isolates and six related Bacillus species for molecular variation. AFLP markers are extremely sensitive to even small sequence variation, using PCR and high-resolution electrophoresis to examine restriction fragments. Using this approach, we examined ca. 6.3% of the Bacillus genome for length mutations and ca. 0.36% for point mutations. Extensive variation was observed among taxa, and both cladistic and phenetic analyses were used to construct a phylogeny of B. anthracis and its closest relatives. This genome-wide analysis of 357 AFLP characters (polymorphic fragments) indicates that B. cereus and B. thuringiensis are the closest taxa to B. anthracis, with B. mycoides slightly more distant. B. subtilis, B. polymyxa, and B. stearothermophilus shared few AFLP markers with B. anthracis and were used as outgroups to root the analysis. In contrast to the variation among taxa, only rare AFLP marker variation was observed within B. anthracis, which may be the most genetically uniform bacterial species known. However, AFLP markers did establish the presence or absence of the pXO1 and pXO2 plasmids and detected 31 polymorphic chromosomal regions among the 79 B. anthracis isolates. Cluster analysis identified two very distinct genetic lineages among the B. anthracis isolates. The level of variation and its geographic distribution are consistent with a historically recent African origin for this pathogenic organism. Based on AFLP marker similarity, the ongoing anthrax epidemic in Canada and the northern United States is due to a single strain introduction that has remained stable over at least 30 years and a 1,000-mile distribution.